Photochemical Transformations Involving Porphyrins and Phthalocyanines - SENGE, MATHIAS (CRC Press, 2012)
Photochemistry of the porphyrins and their relatives has been largely inspired by photosynthetic processes in nature. As a result of this, most current studies generally utilize the chemistry of magnesium and zinc porphyrin analogues. Especially, magnesium tetrapyrrole chelates, i.e. magnesium porphyrins and phthalocyanines have found wide interest. This is primarily related to the biological relevance of magnesium porphyrins in nature, notably in photosynthesis and electron transfer (ET), and thus we will focus on this aspect in this review. Outside these areas not many "true" photochemical studies have been performed with magnesium tetrapyrroles. Although porphyrins and especially phthalocyanines are stable compounds, both will undergo photooxidative degradation or photoexcited ET reactions. An additional problem of magnesium complexes is their low stability in aqueous solution, as they are prone to demetallation. As a result of this, many photochemical studies targeted at modeling the natural situation use the more stable zinc complexes. Zinc derivatives exhibit photochemical properties similar to the natural magnesium derivatives while being more stable and easier to synthesize (Li et al. 1997). Secondly, the propensity of zinc to act as an acceptor atom is used in many supramolecular approaches and/or for the modulation of chromophore properties via axial ligand binding. Thus, due to their biological relevance, technical importance and good stability, substituted zinc tetrapyrrole have found significant use as industrial pigments, electron transfer components, for photochemical transformations and in photobiotechnology. Likewise, industrial attention has been given to the stable copper derivatives and copper tetrapyrroles have found industrial uses for oil desulfurization, as photoconducting agents in photocopiers, deodorants, germicides, optical computer disks, semiconductor devices, photovoltaic cells, optical and electrochemical sensing, and as molecular electronic materials.
CRC Handbook of Organic Photochemistry and Photobiology
PUBLISHED
Keywords: Porphyrins